Empowering the people Jesus, healing, and exorcism - Horsley, Richard A. 1939- (Eugene, OR Cascade Books, 2022)
"In this innovative study, Horsley builds on his earlier works concerning the problematic and misleading categories of "magic" and "miracle" to examine in-depth the meaning and importance of the narratives of healing and exorcism in the Gospels. Incorporating his work on oral performance and turning to important works in medical anthropology, a new image emerges of how these narratives help us re-evaluate Jesus's place in first-century Galilee and Judea. In his exorcisms and healings, Jesus-in-interaction was empowering the villagers in their struggles for renewal of personal and communal dignity in resistance to invasive Roman rule." --
Part I. Beyond modern misunderstandings. Gospel portrayals versus scholarly interpretation -- Miracles and magic: modern misunderstandings -- Understanding exorcism and healing in historical contexts --Part II. The historical context. The political-economic-social context in Roman Palestine -- Sickness and healing, spirit possession and exorcism in Judea and Galilee -- Part III. Understanding and using the gospel stories appropriately as sources. The gospel sources: stories, in performance -- The Markan story -- The series of Jesus speeches -- The Matthean story -- The Lukan story -- Part IV. The effect and significance of exorcisms and healings. The effects of the gospel stories in performance -- The empowerment of Jesus' exorcism and healing.
Includes bibliographical references (pages 487-507) and index
Keywords: Jesus Christ -- Healing; Jesus Christ -- Exorcism; Jesus Christ; Bible -- Commentaries; Bible -- Criticism, interpretation, etc; Bible - Critique, interprétation, etc; Bible; Bible; Healing in the Bible; Medicine in the Bible; Guérison dans la Bible; Médecine dans la Bible; Exorcism; Healing; Healing in the Bible; Medicine in the Bible; Commentaries; Criticism, interpretation, etc